Facets of a Diamond. Notes for a History of the Immediacy in the Italian Criminal Procedure - Marco Nicola Miletti (Revista Brasileira de Direito Processual Penal)
The essay traces some stages in the evolution of the principle of immediacy in the Italian criminal procedure, within the time span between the end of the eighteenth century and Finocchiaro-Aprile’s code (1913). After a brief review of the different definitions of the term and a mention of the distinction between immediacy and orality, the research begins with ideas offered by ‘pioneers’ such as Francesco Mario Pagano and Niccola Nicolini; than it examines the European (French and, especially, German) Literature which had the greatest influence on the Italian one; finally, it studies the Italian post-unitarian criminal science. The latter had to do with a still inquisitional code (1865). For their part, the scholars were by no means compact: the first commentaries and, even more, Carrara’s school considered immediacy a non-negotiable principle of the liberal justice; the positivist school feared that the rule could favour popular and emotional interferences in the trial. The long elaboration of Finocchiaro-Aprile’s code stimulated a heated debate and inserted the criminal procedure studies into the «orality movement» led by Giuseppe Chiovenda.